Analisis Kemampuan Membaca Siswa Pada Pembelajaran Reading Comprehension - Musahrain Musahrain; Nunuk Suryani; Suharno Suharno (Teknodika, 2018)
This study aimed to determine the ability of students’ reading comprehension in grade XI SMA Negeri Kota Bima, the factors that affect the students’ reading comprehension comprehension, as well as obstacles and how to overcome them. The type of research used in this research was qualitative research using observation, interview and documentation study. The data collection technique involved 74 students of class XI in SMA Negeri Kota Bima as respondents. While for data analysis technique, the writer uses triangulation of data and sources. From this research, it resulted: (1) Based on the results of student learning evaluation conducted by teachers during the last 2 years, the average score obtained by students of 60, 28 of them got score with a high value ranges 70-100, and the remaining got 46 scores with a score range of 10-65; (2) Factors that may affect student reading comprehension were internal and external factors; (3) As for some obstacles encountered in this research were: (a) The use of instructional media by teachers was still lacking, (b) the utilization of facilities and infrastructure had not been maximized, (c) the learning resources were still lacking, (d) the student’ motivation was low, (4)The solutions offered were: (a) Maximum utilization of facilities and infrastructure, (b)the use texts in the form of local folklore, (d) using and develop innovative, lightweight, easy and repeatable media of learning.